Ultra-Violet Radiation Has a Limited Impact on Seasonal Differences in the Acropora Muricata Holobiont - van de Water, Jeroen A. J. M.; Courtial, Lucile; Houlbrèque, Fanny; Jacquet, Stéphan; Ferrier-Pagès, Christine (Frontiers in Marine Science, 2018)
Environmental conditions are known to influence corals and their associated communities of microorganisms. However, our insights into the impacts of seasonal changes in ultraviolet radiation (UVR) on both coral physiology and microbiome remain very limited. To address this challenge, we maintained the coral Acropora muricata shaded from UVR or under ambient UVR levels during two contrasting seasons, i.e. summer and winter, and assessed the impact of UVR on the coral holobiont at each season. To this end, we analysed the physiology (e.g. calcification, protein content, photosynthesis-related parameters) and coral microbiota composition, as well as the abundance and composition of the microbial communities and organic matter contents of the surrounding seawater. Our results show major seasonal effects on coral phenotype: (1) a lower host biomass and photosynthesizing, but fast calcifying phenotype in summer, and (2) a higher host biomass and photosynthesizing, but slow calcifying phenotype in winter. UVR had only a significant impact on Symbiodinium functioning. Specifically, high UVR levels reduced photosynthesis efficiency in summer, but an increase in chlorophyll a content may have compensated for this effect. The coral microbiota, which was variable but generally dominated by Endozoicomonas, was not affected by UVR, but its composition differed between seasons. In contrast, UVR had a major, but differential impact on the seawater microbial communities at both seasons. Particularly in summer, bacteria from the Alteromonadaceae were significantly more abundant (15-fold; up to 75%) in seawater under ambient UVR levels. Overall, our study suggests that UVR has only a limited impact on coral holobiont composition and functioning, despite major fluctuations in the surrounding seawater microbiome; seasonal changes in the holobiont are thus mostly driven by other environmental factors.